Analisis Etika Bisnis Terhadap Kebijakan Kenaikan Tarif Dasar Listrik oleh Perusahaan Listrik BUMN - Arya Haydar Zulfikar; Halimah Zahrah; Neng Lisda Saadah; Syakila Fasha Nurdin (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The increase in electricity base tariffs (TDL) in Indonesia is a strategic issue affecting the public and business sector. As a state-owned enterprise, PLN has a responsibility not only in public service but also in applying business ethics. This study aims to analyze the application of ethical principles in the TDL policy. A qualitative inductive method is applied through literature review and document analysis. Thematic analysis focuses on social justice, transparency, corporate social responsibility (CSR), and good corporate governance (GCG). The results indicate that although the policy has economic justification, its implementation still faces ethical issues, especially for vulnerable groups.